Density Functional Theory Investigation into the B and Ga Doped Clean and Water Covered γ-Alumina Surfaces - Lihong Cheng; Tianliang Xu; Wenkui Li; Zhiqin Chen; Jianping Ai; Zehua Zhou; Jianwen Liu (Journal of Chemistry)
The structures and energies of the B and Ga incorporated γ-alumina surface as well as the adsorption of water are investigated using dispersion corrected density functional theory. The results show that the substitution of surface Al atom by B atom is not so favored as Ga atom. The substitution reaction prefers to occur at the tricoordinated A(4) sites. However, the substitution reaction becomes less thermodynamically favored when more Al atoms are substituted by B and Ga atoms on the surface. Moreover, the substitution of bulk Al atoms is not so favored as the Al atoms by B and Ga on the surface. The γ-alumina surface is found to have stronger adsorption ability for water than the B and Ga incorporated surface. The total adsorption energy increases as water coverage increases, while the stepwise adsorption energy decreases. The studies show the coverage of water at 7.5 H2O/nm2 (five H2O molecules per unit cell) can fully cover the active sites and the further water molecule could only be physically adsorbed on the surface.